THE HISTORY OF THE CREATION AND FEATURES OF THE GENRE OF THE WORK "MUNSHAOT" (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the genre of munshaot as one of the most important forms of prose creativity in Uzbek classical literature and the literary, historical and cultural significance of the work "Munshaot" by Alisher Navoi . The study covers the origin of the munshaot genre, its place in the Eastern literary tradition, its features as an epistolic genre, and the combination of formal and literary styles. On the example of the work "Munshaot" by Alisher Navoi, the socio-political life of the Timurid period of the 15th century, the culture of writing and the possibilities of the classical prose language are revealed. The didactic and ethical orientation of the work, features of language and style, compositional structure and influence on subsequent literary traditions are scientifically substantiated. The article aims to highlight the role of "Munshaot" in the history of Uzbek literature and its significance as a source of language, history and culture.
Keywords: Munshaot, Alisher Navoi, classical prose, epistolary genre, correspondence, Oriental written culture, Timurid period, formal and artistic style, juvenile and adultery, didactic and moral ideas.